Promoting Critical Thinking Skills in Education - Ray Suryadi; Ritawati Ritawati (Education Studies and Teaching Journal (EDUTECH), 2024)
This study aims to explore the relationship between project-based learning (PBL) and students' critical thinking skills in various educational contexts. Using comprehensive research methods, researchers investigated the impact of PBL on the development of students' critical thinking skills and evaluated various research approaches used to assess the effectiveness of PBL. The research results show that PBL contributes positively to students' critical thinking skills, with the integration of innovative learning methods such as metacognition and problem-based learning strengthening the positive effects. The implications of these findings for educational practice and future research directions are also discussed.